La carte et le territoire à l’ère numérique - Henri Desbois (Socio, 2015)
Geography has undergone significant changes with the generalisation of digital mapping techniques. In the 1990, their epistemological effects were the subject of extensive discussion in a context of challenge to the concept of objectivity in the humanities and social sciences. These discussions in no way slowed down the adoption of digital methods, enhanced by the attraction of novelty and promoted by a favourable economico-political context. With the GPS, smartphone applications of geo-localisation and online mapping, digital geography is now part of everyday life. Beyond the technological fascination, we must endeavour to understand what vision of the world these new tools produce.